Economic crisis management and challenges: restructuring the Indian economy - Sinha, R.K (ed.) (New Delhi, 1992)
The period since 1990 has been. exceptionally difficult for the Indian economy. It continues to face an unprecedented economic crisis. The new Government led by Mr. P.V. Narasimha Rao moved swiftly to the task of pulling the economy back from the brink of disaster and setting it once more on the path of rapid and sustained growth. It is too early to pronounce a judgement. Yet a careful analysis of the steps taken can indicate the areas of strength and weakness, depth and shallowness, thetoric and reality. This book is a critical analysis in this direction. The book will be helpful in understanding and appreciating the grand debate on India's structural adjustment in over coming the economic crisis.
Keywords: Economic policy-India